2005
DOI: 10.2106/jbjs.d.03049
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Acute Achilles Tendon Ruptures<sbt aid="961641">A Meta-Analysis of Randomized, Controlled Trials</sbt>

Abstract: Therapeutic Level I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
411
0
57

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 373 publications
(474 citation statements)
references
References 37 publications
6
411
0
57
Order By: Relevance
“…Percutaneous repair is becoming a well-accepted modality in the management of acute AT tears [10,39] and yields similar rerupture rates when compared to open techniques [12,21]. The major advantages of percutaneous repair are less iatrogenic damage to normal tissues, less postoperative pain, accurate opposition of the tendon ends minimizing surgical incisions, thus protecting against wound breakdown and wound complications [49], and improved cosmesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Percutaneous repair is becoming a well-accepted modality in the management of acute AT tears [10,39] and yields similar rerupture rates when compared to open techniques [12,21]. The major advantages of percutaneous repair are less iatrogenic damage to normal tissues, less postoperative pain, accurate opposition of the tendon ends minimizing surgical incisions, thus protecting against wound breakdown and wound complications [49], and improved cosmesis.…”
Section: Discussionmentioning
confidence: 99%
“…Acute ruptures of the AT occur most commonly in men in their third and fourth decades of life who participate in sports intermittently [21,33]. The management of AT ruptures has changed with time, as more evidence is available in favor of early weight bearing and early active mobilization [26,34,35], and also for the use of percutaneous techniques instead of open surgery [21,24]. One review of the literature [20] suggested that most patients were around 40 years old, although the ages ranged from 12 to 86 years.…”
Section: Introductionmentioning
confidence: 99%
“…For the purpose of this evaluation, it is important to highlight that non-operative treatment cannot avoid tendon lengthening (22) . In a meta-analysis conducted by Khan et al, including 12 randomized control trials and 800 patients, open surgery was related to lower risk of re-rupture than non-operative treatment however higher risk of other issues, particularly wound problems (23) . Surgical treatment appears to be the technique of option for youths, professional athletes, and delayed ruptures.…”
Section: Treatment (Repair)of Achilles Tendon Injuries:-mentioning
confidence: 99%
“…Furthermore, the advent of early, accelerated functional rehabilitation programs has further compounded decision-making and has created numerous pathways to choose in dealing with acute Achilles tendon ruptures. Historically, many surgeons advocate early operative repair of acute ruptures, citing a lower re-rupture rate [41] of the tendon and improved functional outcomes, particularly with the amount plantar flexion and endurance, over nonsurgical treatment [42]. Conversely, proponents of nonoperative treatment argue that you avoid the increased risks of complications associated with surgical repair.…”
Section: Operative Vs Nonoperative Treatmentmentioning
confidence: 99%
“…In 2002, Bhandari et al [56] pooled the results of 448 patients and reported a relative risk of re-rupture of 0.32 in favor of surgical repair. In 2005 Khan et al [41] published the results of their meta-analysis and found that surgical repair also had a lower rate of re-rupture but that it came at a cost of higher rate of other complications, such as infections, adhesion, wound problems, and disturbed skin sensibility.…”
Section: Operative Vs Nonoperative Treatmentmentioning
confidence: 99%